2001
DOI: 10.1007/s002100000279
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of mercury sulfide in the vestibular ocular reflex system of guinea pigs

Abstract: A traditional Chinese mineral medicine, cinnabar, naturally occurring mercuric sulfide (HgS), is still occasionally prescribed, but the neurotoxic effects of HgS have not been elucidated. In this paper, an animal model of the purified HgS intoxication was established in guinea pigs in order to study neurotoxicity and pathophysiology of the vestibular ocular reflex system (VOR). Guinea pigs were dosed with HgS by gastric gavage (0.01, 0.1 and 1.0 g/kg per day) for 7 consecutive days. By means of caloric testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Cinnabar might induce an irreversible injury of the brain at the higher dose of 5 g/kg BW over a 10-day experimental duration. The cerebellum was more sensitive to cinnabar induction than cerebrum, which was consistent with a reported suggestion that cerebellum is one of the vulnerable sites of action of HgS (Chuu et al, 2001).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Cinnabar might induce an irreversible injury of the brain at the higher dose of 5 g/kg BW over a 10-day experimental duration. The cerebellum was more sensitive to cinnabar induction than cerebrum, which was consistent with a reported suggestion that cerebellum is one of the vulnerable sites of action of HgS (Chuu et al, 2001).…”
Section: Discussionsupporting
confidence: 89%
“…HgS could also induce dysfunctions of both vestibule-ocular reflex (VOR) system and the motor performance in guinea pigs (Chuu et al, 2001;Young et al, 2002). Despite these findings, there are few studies reporting the metabolic profiling of neurotoxicity of cinnabar by NMR.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our laboratory, we have established the caloric test coupled with ENG recordings for assessing the function of the VOR system of guinea pigs (Young et al, 1991). We have shown that this system is capable of monitoring the toxic effects of mercury sulfide (Chuu et al, 2001). The caloric test was performed after 14 consecutive days of administration.…”
Section: Caloric Testmentioning
confidence: 99%
“…The aging effect on the caloric test leads to the significantly decreased SPV, rather than increased SPV (caloric hyperfunction) (Mulch and Petermann, 1979). Since bilateral caloric hyperfunction is caused by either cerebellar disinhibition or psychosomatic disorder (Young and Nomura, 1995), neurotoxicity to the Purkinje cells of the cerebellum could be due to exposure to alcohol (Seilicovich et al, 1985), metals (Chuu et al, 2001), chemicals (Odkvist et al 1983), or drugs (Young and Huang, 2001). Our 10 hairdresser patients reported here all denied of abuse of alcohol, cigarettes, or drugs.…”
Section: Figmentioning
confidence: 99%